Assessment of the environmentally minimum lake level based on hydromorphological features (2023)
Doulgeris C., P. Georgiou, A. Apostolakis, D. Papadimos, D. Zervas, O. Petriki, D. Bobori, D. Papamichail, V. Antonopoulos, C. Farcas, and P. Stålnacke. 2017. Assessment of the environmentally minimum lake level based on hydromorphological features. European Water, 58: 197–202